2019
DOI: 10.1155/2019/2639248
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 Detects Clinically Significant Fibrosis in Patients with Chronic Viral Hepatitis C

Abstract: Pentraxin 3 (PTX3) plays a pathogenic role in experimental models of chronic liver injury and contributes to the progression of fibrosis. The detection of advanced fibrosis (METAVIR F≥3) is important to identify patients who are in urgent need of antiviral treatments versus those whose treatment could be deferred (F≥2). The aim was to assess the diagnostic value of PTX3 as a potential biomarker for clinically significant and advanced fibrosis. PTX3 associations with biochemical and histological parameters of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In liver diseases, PTX3 levels were markedly higher in NASH than in simple steatosis non-NASH patients 30,31 . PTX3 levels were also related to the severity of liver fibrosis in NASH 30 and HCV infection 34 . It is suggested that PTX3 is involved in pathogenesis of hepatic inflammation and fibrosis which are common milieu at the origin of HCC 43 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In liver diseases, PTX3 levels were markedly higher in NASH than in simple steatosis non-NASH patients 30,31 . PTX3 levels were also related to the severity of liver fibrosis in NASH 30 and HCV infection 34 . It is suggested that PTX3 is involved in pathogenesis of hepatic inflammation and fibrosis which are common milieu at the origin of HCC 43 .…”
Section: Discussionmentioning
confidence: 98%
“…Hepatic and plasma PTX3 was raised in alcoholic hepatitis patients and PTX3 expression was related to the disease severity and short-term mortality 33 . Serum PTX3 was clinically shown to have valid diagnostic accuracy as a marker of fibrosis in chronic hepatitis C virus (HCV) infection 34 and increased PTX3 plasma level was a risk factor for HCC occurrence in chronic HCV infection 35 . Furthermore, PTX3 was shown to be able to promote HCC progression and high PTX3 expression in tumor tissues was related to unfavorable prognosis in HCC patients 36 .…”
Section: Serum Pentraxin 3 As a Biomarker Of Hepatocellular Carcinomamentioning
confidence: 99%
“…MAFLD is a systemic disease that increases risk of both hepatic and extrahepatic complications, with cardiovascular disease is the main cause of death in these patients, which is also associated with severity of liver brosis (4,19). CIMT is a standard method for evaluation of early general atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…WT fibroblasts were found to preferentially upregulate pro-fibrotic gene expression compared to those from IQGAP1 +/− MSI capsules. We observed elevation of Acta2 (encoding smooth muscle alpha actin, aSMA), as well as Cxcl5, Cxcl2, Saa3, and Ptx3, all of which have been implicated in fibrotic pathologies encompassing pulmonary, hepatic, and myocardial fibrosis [42][43][44][45] (Figure 4B). Specifically, the CXCL-family of cytokines have been shown to positively influence myofibroblast phenoconversion and ECM deposition.…”
Section: Iqgap1 Deficient Mice Display Decreased Mechanical Signaling Inflammation and Fibrosismentioning
confidence: 99%